E-Money: Tinjauan Fiqih Kontemporer - Nunung Nurlaela (Kopertais Wilayah III Yogyakarta, 2022)
One of the problems of contemporary islamic economy is the development of non-cash payment instruments, especially e-money. This research is a qualitative study to obtain legal status for non-cash transactions using e-money. Clarity of legal status regarding the use of e-money is of course expected to accelerate the process of adoption of Muslims. The fact of e-money is like a debit card, because the money used in electronic money is consumer money, not debt accompanied by usury, so the stastus for using electronic money is actually a “hawalah” contract. Electronic money in the “hawalah” contract can be called “muhal bih” (debt transferred). Thus, the issuance of cards that function as money like this alloweb by sharia law. So, the administration fee and manufacturing of the cards, allowed too. In addition, there is no “gharar” in this electronic money. Keywords: e-money, contemporary jurisprudence, sharia economy, noncash transactions.